Stock Price Dynamics of LQ45 Companies: The Effects of DER, PER, DPS, and the Role of Inflation as an Intervening Variable - Siti Nur Fatimah Putri; Nurul Nabila; Tasya Wulan Dari; Joni Hendra K (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the effects of the Debt-to-Equity Ratio (DER), Price-to-Earnings Ratio (PER), and Dividend Per Share (DPS) on the share prices of companies listed on the LQ45 index, with Inflation as an intervening variable. This research examines how corporate fundamentals and macroeconomic conditions influence share price formation in highly liquid companies in the Indonesian capital market. This study employs a quantitative approach using secondary data from the financial statements of LQ45 companies for the period 2020–2024, along with inflation data from Statistics Indonesia (BPS). Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4 software. The sample was selected through purposive sampling, resulting in 11 companies consistently listed in the LQ45 index during the observation period. The results indicate that Dividend Per Share (DPS) has a positive and significant effect on stock prices, suggesting that dividend distribution policy remains an important consideration for investors in making investment decisions. Furthermore, Inflation does not significantly affect stock prices and cannot mediate the relationships among DER, PER, and DPS. These findings have practical implications for companies, particularly LQ45 firms, to prioritize dividend policies to enhance investor confidence and maintain stock price stability. Theoretically, this study supports the view that investors in large-capitalization firms tend to place greater emphasis on internal corporate fundamentals rather than short-term macroeconomic factors such as Inflation.